Assessing the Effect of GGBFS Content on Mechanical and Durability Properties of High-Strength Mortars - Si-Huy Ngo; Ngoc-Tan Nguyen; Xuan-Hien Nguyen (Salehan Institute of Higher Education, 2022)
As a large amount of steel is produced for the industrialization and modernization of Vietnam, a correspondingly large quantity of steel slag is also released annually. Besides, the demand for mortar is increasing due to urbanization, especially for the high-strength and durability mortar used for important constructions and structures in aggressive environmental areas. This study aims to carry out further research into high-strength mortars incorporating ground granulated blast furnace slag (GGBFS). The control mixture was designed with a water-to-binder ratio of 0.2, and the amount of silica fume used was equal to 25% of the total binder amount by mass. Four other mixtures were designed using GGBFS to substitute for 15, 30, 45, and 60% of cement by mass. The engineering properties of fresh and hardened mortars were comprehensively investigated, especially the durability properties. The microstructure of these mortars was also examined using scanning electron microscopy. Test results show that replacing 15 or 30% of cement with GGBFS yields an improvement in mortar's strength and durability properties. All the mortars in this study show excellent qualities with high strength, low water absorption, and high resistance to chloride attack. Moreover, the presence of GGBFS reduces the shrinkage of mortar caused by the drying process. Doi: 10.28991/CEJ-2022-08-05-07 Full Text: PDF